Bring me back [compact disc, unabridged] - Paris, B. A. (Macmillan Audio, 2018)
Ten years after his girlfriend, Layla, was abducted, Finn is engaged and happy. But has his first love somehow come back? Or is the person who took her playing games with his mind?